Pemberdayaan Kelompok Masyarakat Desa Karang Anyar untuk Meningkatkan Pendapatan dalam Produksi Usaha Rengginang - Ramsul Nababan; Jufri Darma; Kaerul Saleh; Ali Nurman (Universitas Medan Area, 2020)
Community Service Activities aims to improve the quality of financial bookkeeping management, the quality of packaging and trademarks for Small and Medium Enterprises (SMEs) in Karang Anyar Village. The problems faced by Partners here are; (1) financial management has not been recorded continuously and is manual without having a record between capital and profits, (2) rengginang packaging using kiloan plastic so that the packaging is easily torn, and the packaging is not attractive and does not yet have a trademark. The solution offered here, Partners are given training, education, assistance, socialization, and the delivery of Appropriate Technology (TTG) regarding the problems faced by Partners. The method of implementing the service program will be carried out in a gradual, sustainable and comprehensive approach through direct communication or through intensive communication tools with partners, so that the implementation of activities can be carried out in a guided manner, with the primary aim of improving the community's economy in managing Small and Medium Enterprises (SMEs) ) with Rengginang food business.